The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1016/j.ssmph.2021.100948
|View full text |Cite
|
Sign up to set email alerts
|

Association between internet addiction and loneliness across the world: A meta-analysis and systematic review

Abstract: There might be an association between Internet addiction (IA) and loneliness; however, inconsistent evidence suggests that the severity of this association remains unclear. This study was conducted to assess the association between IA and loneliness. A systematic literature search was conducted in four online databases, including PubMed (MESH terms), Web of Science, Scopus, and Embase. Observational studies measuring the association between IA and loneliness were screened and included in this review. A meta-an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 23 publications
3
20
0
Order By: Relevance
“…Should these adolescents persist in an escapist coping strategy, favoring an addiction to the Internet while being unable to create social ties online, they will get caught in a vicious circle, increasing their feeling of loneliness and the risk of developing suicidal ideation. This concurs with the observation made in the literature between the degree of addiction to the Internet and the feeling of loneliness, which is a linear association [ 43 ].…”
Section: Discussionsupporting
confidence: 92%
“…Should these adolescents persist in an escapist coping strategy, favoring an addiction to the Internet while being unable to create social ties online, they will get caught in a vicious circle, increasing their feeling of loneliness and the risk of developing suicidal ideation. This concurs with the observation made in the literature between the degree of addiction to the Internet and the feeling of loneliness, which is a linear association [ 43 ].…”
Section: Discussionsupporting
confidence: 92%
“…Differences in terms of occupation and family structure in the included populations might be another factor potentially explaining the higher prevalence of IA among Africans in our study. Indeed, IA has been associated with detached family relationship and loneliness ( Hassan, Alam, Wahab, & Hawlader, 2020 ; Mozafar Saadati, Mirzaei, Okhovat, & Khodamoradi, 2021 ; Shek, Zhu, & Dou, 2019 ), patterns possibly encountered among university students in Africa (84% of our meta-analysis population), especially those who move from rural areas to study in urban settings ( Bozoglan, Demirer, & Sahin, 2013 ; Le Roux, 2004 ). However, our higher prevalence does not seem to be parallel to the internet penetration rate.…”
Section: Discussionmentioning
confidence: 83%
“…These findings supported the past evidence on the key role exerted by insecure attachment to parents on the development of IA during young adulthood [ 132 ], as well as among university students. Coherently, a young adult university student who perceived their relationship with their parents as characterized by a lack of closeness, warmth, and emotional availability may tend to excessively use the internet to seek emotional and social support in online relationships [ 72 , 74 , 133 ]. On the other hand, the results of our study showed that the quality of the relationships with mothers and fathers exerted a different and peculiar influence on the young adult university students’ level of IA during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Trumello et al [ 71 ] showed that there were also significant associations between attachment insecurity and IA during the COVID-19 pandemic. Overall, this body of research suggests that young adult university students may excessively use the internet as a strategy to cope with the distress resulting from insecure relationships with their attachment figures [ 72 , 73 ] and to seek social support from the virtual world [ 74 ]. Interestingly, the possible mediation role played by the young adults’ psychopathological symptoms on the relationship between the quality of their relationships with parents and peers and the IA levels has recently been suggested [ 46 , 48 , 75 ].…”
Section: Introductionmentioning
confidence: 99%